Exploring Differentiated Learning Strategies to Respond to Differences in Students' Level of Understanding of Metal Inorganic Chemistry Course - Napitupulu*, Mery; Walanda, Daud K; Griffiths, Zoe; Nurmayanti, Yuli; Poba, Detris (Jurnal IPA & Pembelajaran IPA, 2025)
Differentiated learning refers to educational schemes and materials individually developed about the varied needs of each student to improve knowledge understanding as individuals, as well as participation involvement. The study applied differentiated learning in the metal inorganic chemistry class of chemistry education to address student understanding variability. These strategies and their effect on student performance were studied through observations, surveys, and interviews in a mixed-method design. The findings portrayed that the application of differentiated learning helps boost the student's performance in understanding the concepts inorganic chemistry of metals. Additionally, the students showed higher satisfactions and engagements when the instructor incorporated different teaching modes, materials (videos, presentation materials, and books), and practical use of examples. Group discussion and collaborative learning among the students helped them better understanding and retention of the knowledge of metal inorganic chemistry